2015
DOI: 10.1088/1475-7516/2015/05/056
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing dark matter from unresolved point sources in the Inner Galaxy with photon statistics

Abstract: Data from the Fermi Large Area Telescope suggests that there is an extended excess of GeV gamma-ray photons in the Inner Galaxy. Identifying potential astrophysical sources that contribute to this excess is an important step in verifying whether the signal originates from annihilating dark matter. In this paper, we focus on the potential contribution of unresolved point sources, such as millisecond pulsars (MSPs). We propose that the statistics of the photons-in particular, the flux probability density functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 145 publications
(289 reference statements)
1
89
0
Order By: Relevance
“…We follow the procedure outlined in the literature [35,[50][51][52] to calculate the photon-count probability distribution in each pixel for the combined template model as 8 To facilitate comparison with the previous work of [35], for the NPTF analysis we use a GCE template constructed from an NFW with γ =1.25, which is the value used in that reference. We find changing this to 1.14 has a much smaller impact than the other sources of uncertainties in our analysis.…”
Section: B Inner Galaxy -Non-poissonian Template Fittingmentioning
confidence: 99%
See 2 more Smart Citations
“…We follow the procedure outlined in the literature [35,[50][51][52] to calculate the photon-count probability distribution in each pixel for the combined template model as 8 To facilitate comparison with the previous work of [35], for the NPTF analysis we use a GCE template constructed from an NFW with γ =1.25, which is the value used in that reference. We find changing this to 1.14 has a much smaller impact than the other sources of uncertainties in our analysis.…”
Section: B Inner Galaxy -Non-poissonian Template Fittingmentioning
confidence: 99%
“…Numerous studies have cast doubt on this interpretation by a comparison of the luminosity distribution of γ-ray pulsars observed in the Galactic plane with the lack of individually detected γ-ray pulsars near the Galactic center [44,45,68,69] (see, however, [30,31,33,34,37] for alternative arguments). On the other hand, recent studies of the fluctuations in the γ-ray data have found significant "hotspots" consistent with a population of sub-threshold point sources, potentially indicative of a significant pulsar contribution [36,51]. While significant work remains in assessing the fit of pulsar models to the Galactic center data, it is worth investigating the emission from such a pulsar population at high γ-ray energies.…”
Section: Fig 11mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it remains unclear whether this signal arises from DM annihilation rather than from a currently unknown contribution from astrophysics such as a large population of milli-second pulsars, cosmic-ray (CR) proton or electron outbursts, additional cosmic ray sources, and/or emission from a stellar over-density in the Galactic bulge [11,16,[18][19][20][21][22][23]. An interesting development is the use of statistical tools which indicate that GeV photons from the direction of the inner galaxy region show significantly more clustering than would be expected from Poisson noise from smooth components [24][25][26][27]. However, it remains difficult with the current models to disentangle whether this feature represents a property of the excess itself, or unmodelled variation in the background components [28].…”
Section: Introductionmentioning
confidence: 99%
“…the past activity of the supermassive black hole lying in the center of the galaxy [67,68]. On the other hand, dwarf spheroidal galaxies are considered as very interesting targets to look for a dark matter signal.…”
Section: Jhep11(2017)132mentioning
confidence: 99%